Hands-on activity to facilitate the teaching – learning process of discrete simulation topics - Zuluaga, Carlos Mauricio; Gómez Suta, Manuela del Pilar (Scientia et Technica, 2018)
This article presents a proposal of a hands-on activity to facilitate the teaching - learning process in thematic and computational instruments associated with Discrete Simulation. At first, the theoretical support of the pedagogical methodology used for its design is presented and basic notions of the themes that can be explored in the hands-on activity are presented. Subsequently it presents the development of the proposal and the resulting simulation model, which can be achieved by executing the pedagogical environment exposed. Finally, some conclusions and considerations are developed.